The Effect of Transformational Leadership on Organizational Creativity: The Mediating Role of Innovation Culture in Public Sector Organizations - Muh Irpan; Siti Nurmayanti; Lalu Hamdani Husnan (LP2M IAIN Palopo, 2026)
This study examines the influence of transformational leadership on organizational creativity with innovation culture as a mediating variable among employees of the Land Transportation Management Center (BPTD) Class II, West Nusa Tenggara Province, Indonesia. Employing a quantitative causal research design, data were collected from 176 respondents selected through proportional stratified random sampling from a population of 312 employees. Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS was used for data analysis. The results demonstrate that: (1) transformational leadership exerts a significant positive direct effect on organizational creativity (β = 0.221, p = 0.003); (2) transformational leadership significantly and positively influences innovation culture (β = 0.862, p = 0.000); (3) innovation culture significantly and positively affects organizational creativity (β = 0.681, p = 0.000); and (4) innovation culture partially mediates the relationship between transformational leadership and organizational creativity (indirect effect = 0.587, p = 0.000). These findings reveal that transformational leadership enhances organizational creativity not only directly but also indirectly through the cultivation of an innovation-oriented organizational culture. This study contributes to the public sector management literature by empirically demonstrating the critical mediating role of innovation culture in translating transformational leadership behaviors into creative organizational outcomes within a bureaucratic government institution.